External debt and unemployment nexus: Evidence from West Africa - Elijah Abasifreke P. Udoh; Anthony O. Onah (West African Journal of Monetary and Economic Integration, 2025)
This study examines the dynamic relationship between external debt and unemployment in West Africa, employing the Panel Autoregressive Distributed Lag (P-ARDL) method with the Pooled Mean Group (PMG) estimator. Annual data from 16 West African countries (1991-2021) were analysed. The results reveal a critical duality where external debt has a positive and marginally significant short-run impact on unemployment, but no statistically significant long-run relationship. This indicates that while debt accumulation may create immediate labour market pressures, its long-term effect on structural unemployment is conditional on institutional factors and debt utilisation efficiency. Control variables show inflation has a significant negative long-run relationship with unemployment, while GDP growth shows a positive long- run association, suggesting patterns of "jobless growth" in the region. The findings imply that West African governments have not consistently harnessed external borrowing for sustainable job creation. We recommend institutional reforms to explicitly link debt governance to employment outcomes, strategic investment in labour-intensive sectors, and enhanced regional coordination to transform external debt into a catalyst for inclusive growth.
Keywords: E24; F34; H63; J21; J64; 330; External Debt; Unemployment; Output; GDP Growth; Population Growth; Inflation; Autoregressive Distributed Lag (ARDL); Pooled Mean Group (PMG